Customer satisfaction relationship marketing and competitive advantage : a case of MISC Agencies Sdn Bhd Kota Kinabalu, Sabah / Imelda Albert Gisip, Carlmila Freddie J. Simol and Suzie Mohammad - Albert Gisip, Imelda; Freddie J. Simol, Carlmila; Mohammad, Suzie (2008)
The tenets of relationship marketing are useful in understanding the success of a service provider. Companies operate in highly competitive climate and offer a wide variety of new products and services to both individual and business firms. Today, companies find themselves facing more aggressive competition and unlimited opportunities. One industry where service performance is paramount is the shipping industry. Customers depend on shipping firms to manage a bundle of service activities. For example, if shipping firm fails to complete the complex customer documentation accurately or fails to deliver the goods on time, the customer may suffer dramatically in terms of sales and customerfirm relationship may suffer resulting customer to switch service provider. Hence, an essential ingredient in successful relationship marketing is to keep the customer satisfied on a long-term basis. The key is to develop, maintain and enhance the dynamics of a relationship with a client; the end result will likely be a loyal customer. Unfortunately, except for some works in general shipping relationship strategy literature, little attention has been paid to the specific shipping industry. Therefore to date, there is a poor understanding of any role of relationships in shipping industry. The purpose of this study is to identify reasons for choosing MISC as shipping service provider and to rate MISC's customers' satisfaction level on specified service elements in bid to strengthen its relationship marketing strategy. This research therefore included a measure of customer's evaluation of the service provided by MISC. A set of questionnaire was distributed to 38 respondents. In order to analyze the findings factor analysis and chisquare test were performed to produce more sensitive results. The result of this research revealed that the main reasons MISC is chosen as the most preferred shipping company include good relationship, good service and competitive freight rates. However, findings also revealed that level of satisfaction among respondents who uses other than MISC's services for service elements in terms of freight rates, service personnel and promptness of shipment are found to be fair and below. These are the main areas that could be consideredfor further improvement by MISC.